Registered owner v/s material owner ¿A change of paradigm? Commentary to the Judgment 1376-2017 Civil of the Ilustrious Court of Appeals of Conception (Justicia &Derecho, 2020)
The purpose of this jurisprudence commentary is to analyze a ruling issued by the illustrious Court of Appeals of Concepción, in it the judgment of said court knowing of a case in which a claiming action is deduced by the non-owner against the non-owner, they decide not to give rise to the claiming action and fail in favor of the property owner of the property, changing in this way the prevailing criteria in our jurisprudence which in the past preferred the registered holder over the material holder.
Keywords: Registered posession; material possession; purchasing prescription